Consider the equation 3p – 7 + p = 13. What is the resulting equation after the first step in the solution?
2 answers:
The first step would be to combine like terms which is 3p and p so your equation would look like:
4p - 7 = 13
In the second step you would add 7 to both sides which would give you:
4p = 20
The third and last step would be to divide both sides with 4 which would give you your answer:
p = 5
First p=23 and because if u do the math right that is what u should get
You might be interested in
Answer:
hmmm not sure
Step-by-step explanation:
try mulitply the numbers
Answer:
54
Step-by-step explanation:
x-1=3
2xy=24
3+24=27
27·2=54
Use pythagora's theorem to test if it is a right triangle
c^2 = a^2 + b^2
65^2 = 52^2 + 43^2
4225 = 2704 + 1849
4225 =/= 4553
therefore it is not a right triangle as it does not comply to pythagora's theorem
Answer:
Sure
Step-by-step explanation:
I can't answer this question without a picture of the lines.